Aplikasi Manajemen Biodata Mahasiswa Berbasis Web Menggunakan HTML, CSS, Javascript, Dan LocalStorage - Yusni Yusni; Muh. Arfah Wahlil Pratama; Adelia Asmarani; Listi Aulia; Annisa Annisa; Kharismatul Khomsiah; Serli Serli (Plexi Digital Indonesia, 2026)
This research aims to design and implement a web-based student biodata management application equipped with a login system and CRUD (Create, Read, Update, Delete) features. Manual student biodata management still has several limitations, such as inefficient data recording, risk of data loss, and difficulty in updating information. Therefore, a web-based application is proposed as a simple solution to improve the effectiveness of student data management. The application was developed using HTML to structure the pages, CSS to design an interface resembling a laptop screen, and JavaScript to process the application logic. Data storage was implemented using the browser’s LocalStorage, allowing the application to run without a server or external database. The login system functions as an access control mechanism before users enter the main biodata management page. The testing results show that the application can perform login authentication, input student biodata, save data, display data in a table, and edit or delete data effectively. Data stored in LocalStorage remain available even when the web page is reloaded or the browser is closed. In addition, the simple and structured interface makes the application easy to operate. Based on these results, this web-based student biodata management application can be used as a simple tool for managing student data and as a learning medium for understanding basic web application development, especially the integration of user interface design, programming logic, and client-side data storage.